2007
DOI: 10.1021/jp066062e
|View full text |Cite
|
Sign up to set email alerts
|

CH3Br Structures on Pt(111):  Kinetically Controlled Self-Assembly of Weakly Adsorbed Dipolar Molecules

Abstract: Methyl bromide is a rodlike molecule with a large 1.8 D dipole moment that physisorbs on Pt(111) with its Br end preferentially bound to the surface. The kinetically controlled self-assembly of several ordered CH3Br structures following molecular adsorption at a surface temperature of 20 K and various annealing procedures is revealed by scanning tunneling microscopy (STM). Thermal programmed desorption (TPD) and reflection absorption infrared spectroscopy (RAIRS) provide complementary evidence for kinetic cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Studies of CH 3 Br adsorption on Pt (111) by reflection absorption infrared, thermal programmed desorption spectroscopies, and scanning tunneling microscopy demonstrated that at low coverages, bromomethane occupies only the top sites while with an increase in coverage, less stable multicoordinate sites start to be taken [31,33]. The preferred orientation of CH 3 Br at the saturation coverage of the 0.22-0.25 monolayer (ML) was aligned along the surface normal [31,33,92], and CH 3 Br bound to Pt through Br with a symmetryof less than C 3v [93]. The adsorption energy of CH 3 Br decreases monotonically from 0.62 eV at the 0.12 ML to 0.33 eV at the 0.22 ML [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of CH 3 Br adsorption on Pt (111) by reflection absorption infrared, thermal programmed desorption spectroscopies, and scanning tunneling microscopy demonstrated that at low coverages, bromomethane occupies only the top sites while with an increase in coverage, less stable multicoordinate sites start to be taken [31,33]. The preferred orientation of CH 3 Br at the saturation coverage of the 0.22-0.25 monolayer (ML) was aligned along the surface normal [31,33,92], and CH 3 Br bound to Pt through Br with a symmetryof less than C 3v [93]. The adsorption energy of CH 3 Br decreases monotonically from 0.62 eV at the 0.12 ML to 0.33 eV at the 0.22 ML [31].…”
Section: Discussionmentioning
confidence: 99%
“…Its hydrolytic half-life ranges between 20 and 38 days depending on the temperature and pH [28][29][30]. There are a few studies devoted to the adsorption of bromomethane on Pt [31][32][33], while there isa lack of studies on the electrochemical behavior of CH 3 Br in aqueous solutions. However,the adsorption of related species such as Br on Pt and their impactson hydrogen oxidation and oxygen reduction were previously investigated and published [34][35][36][37][38][39][40][41][42][43][44][45][46].…”
Section: Introductionmentioning
confidence: 99%
“…Under low temperature, low coverages of physisorbed bromomethane tend to lie on the Pt(111) surface [20]. When bromomethane adsorbs on H-covered Pt(111), the desorbed products include CH 4 and HBr [21].…”
Section: Introductionmentioning
confidence: 99%